2007
DOI: 10.1007/s00787-007-0620-5
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone versus haloperidol in children and adolescents with AD

Abstract: Risperidone was found to be more effective than haloperidol in the treatment of behavioral symptoms, impulsivity, language skills, and impaired social relations in children with AD. These results demonstrated that both drugs were safe and well tolerated in the treatment of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 31 publications
0
40
0
2
Order By: Relevance
“…Risperidone was also found to be superior to haloperidol in a head-tohead trial using ABC-Total. 45 On the Childhood Psychiatric Rating Scale, clomipramine, 46 naltrexone, 47 and a vitamin and mineral supplement (containing 19 vitamins and 9 minerals) 48 revealed improvement as compared with placebo. Highdose pyridoxine and magnesium (HDPM) 49 and tetrahydrobiopterin 50 were not statistically distinguishable from placebo.…”
Section: Effi Cacymentioning
confidence: 98%
“…Risperidone was also found to be superior to haloperidol in a head-tohead trial using ABC-Total. 45 On the Childhood Psychiatric Rating Scale, clomipramine, 46 naltrexone, 47 and a vitamin and mineral supplement (containing 19 vitamins and 9 minerals) 48 revealed improvement as compared with placebo. Highdose pyridoxine and magnesium (HDPM) 49 and tetrahydrobiopterin 50 were not statistically distinguishable from placebo.…”
Section: Effi Cacymentioning
confidence: 98%
“…These strong studies suggest there may be a role for haloperidol in cases of severe, refractory negative behaviors. Miral et al (2008) compared haloperidol to risperidone in a head-to-head investigation. This study obtained only adequate research strength due, in part, to use of a non-systematic diagnostic system for ASD.…”
Section: Haloperidolmentioning
confidence: 99%
“…There are no described molecular mechanisms that are affected by (n − 3) fatty acids in autism, and the evidence that any nutritional or pharmacological component can produce any improvement is derived from a group of pilot studies (Chez et al, 2007;Dosman et al, 2007;Miral et al, 2008). One preliminary study found that average total levels of omega-3 (n−3 PUFAs) in the autistic children were about 20% lower than mentally retarded children used as controls.…”
Section: Discussionmentioning
confidence: 99%